2021
DOI: 10.1186/s12951-021-00823-6
|View full text |Cite
|
Sign up to set email alerts
|

MSCs-engineered biomimetic PMAA nanomedicines for multiple bioimaging-guided and photothermal-enhanced radiotherapy of NSCLC

Abstract: Background The recently developed biomimetic strategy is one of the mostly effective strategies for improving the theranostic efficacy of diverse nanomedicines, because nanoparticles coated with cell membranes can disguise as “self”, evade the surveillance of the immune system, and accumulate to the tumor sites actively. Results Herein, we utilized mesenchymal stem cell memabranes (MSCs) to coat polymethacrylic acid (PMAA) nanoparticles loaded with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Several studies have confirmed the importance of the biological functions of MSCs in the progression of NSCLC (Fregni et al, 2018;Gu et al, 2020;Liang et al, 2020;Liu et al, 2021;Yin et al, 2021). MSCs are known to cause transcriptional changes in lung cancer cells, leading to increased expression of MMP9.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies have confirmed the importance of the biological functions of MSCs in the progression of NSCLC (Fregni et al, 2018;Gu et al, 2020;Liang et al, 2020;Liu et al, 2021;Yin et al, 2021). MSCs are known to cause transcriptional changes in lung cancer cells, leading to increased expression of MMP9.…”
Section: Discussionmentioning
confidence: 91%
“…TME dynamics are inseparable from the progression of NSCLC. MSCs are an important component of the TME ( Zhao et al, 2018 ; Zheng et al, 2020 ; Yin et al, 2021 ). MSC-conditioned medium can promote EMT, invasion, and migration of lung cancer cells, and can inhibit cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Yin et al utilized MSCs membrane to coat polymethacrylic acid (PMAA), which was loaded with iron and cypate, to structure Cyp-PMAA-Fe@MSCs. This carrier not only had high stability and good tumor accumulation, but also had excellent photothermal conversion efficiency, which was used in photothermal therapy of lung cancer( Yin et al, 2021 ).…”
Section: Cell Sources For Preparing Biomimetic Membrane Carriersmentioning
confidence: 99%
“…As an essential element for the human body, iron plays a central role in the process of DNA replication and is also an auxiliary factor for heme ( 21 , 22 ). Moreover, the application of iron-containing contrast agents in magnetic resonance imaging (MRI) has gradually matured due to the advantages of their good imaging effects, low toxicity, and low price ( 23 , 24 ). On the other hand, a large number of studies have shown that IR780 can be effectively imaged after high-intensity infrared radiation to mediate PTT, PDT and SDT in tumor tissue ( 25 ).…”
Section: Introductionmentioning
confidence: 99%